In search of the talkative public - Dahlgren, Peter (Javnost (Ljubljana), 2002)
Theories of democracy consider communicative interaction among citizens central. In recent years the idea of deliberative democracy has galvanised elements of political theory with perspectives on communication. This concept emerges to a large extent from the Habermasian trajectory and links currents from theories of civil society and citizenship. It has thus a rather forceful normative dimension. However, there are difficulties; and the aim of the article is to probe the notion of deliberative democracy by framing it in ways that may render it more useful for both theoretical and empirical work. The article begins with a quick interpretation of the theoretical background. From there the author discusses some current issues of conceptualisation, in particular if such talk should be seen as a part of everyday conversation or a special mode of interaction. These definitional issues set the stage for an examination of two recent empirical contributions. In the final section, the article attempts to situate deliberative democracy within an analytic framework of civic culture. Deliberative democracy, or more simply, discussion, becomes one of six dimensions of civic culture.
Keywords: teorija komunikacij; javnost; civil society; civilna družba; democracy; demokracija